Maxillary dentoalveolar assessment following retraction of maxillary incisors: a preliminary study - Oliveira,Tiago Maia Fernandes (2016)
ABSTRACT Objective: The aim of this preliminary study was to assess changes in tooth length and alveolar thickness following retraction of maxillary incisors. Methods: A total of 11 patients presenting severe maxillary dentoalveolar protrusion revealed by initial (T1) cone-beam computed tomography (CBCT), and whose treatment plan included extraction of maxillary first premolars and retraction of maxillary incisors, were selected and submitted to CBCT examination one month after the end of incisors retraction (T2). The premaxilla was assessed through seven axial slices by means of Dolphin ImagingTM software. In each of these slices, five measurements of the distance from the buccal cortical bone to the palatal cortical bone were performed. Tooth length of maxillary incisors (n = 44) was also measured in sagittal slices. Measurements were repeated after a two-week interval, and intraclass correlation coefficient (ICC) was used to test examiner calibration. Wilcoxon test was used to detect differences in measurements performed at the two time intervals. Results: The ICC was satisfactory for tooth length (0.890) and for premaxilla alveolar thickness measurements (0.980). Analysis of data showed no statistically significant differences (p > 0.05) in tooth length or alveolar thickness between the two-time intervals assessed. Conclusion: The force used in retraction of maxillary incisors in this research did not promote significant changes in tooth length of maxillary incisors or in premaxilla alveolar thickness.